1968
DOI: 10.1136/thx.23.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Maximal acid output and oesophagitis in hiatus hernia

Abstract: It has been suggested (Casten, Bernhang, Nach, and Spinzia, 1963) that patients with symptomatic sliding hiatus hernia have a higher acid output than the normal patient, but this has recently been disputed by Williams, Lawrie, and Forrest (1967). These latter workers found that there is no significant increase in maximal acid output in patients with sliding hiatus hernia. Aylwin (1953) demonstrated a correlation between the degree of oesophagitis in sliding hiatus hernia and the enzyme activity of juices bathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1972
1972
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Previous reports (Williams, Lawrie and Forrest, 1967;Squire, Glick and Benn, 1968;Stol, Murphy and Collis, 1974) involving a small number of selected cases have cast doubt on the role of gastric acid hypersecretion in oesophagitis.…”
Section: Introductionmentioning
confidence: 95%
“…Previous reports (Williams, Lawrie and Forrest, 1967;Squire, Glick and Benn, 1968;Stol, Murphy and Collis, 1974) involving a small number of selected cases have cast doubt on the role of gastric acid hypersecretion in oesophagitis.…”
Section: Introductionmentioning
confidence: 95%
“…, 1955;Winkelstein, 1957;Tuttle et al, 1960;Casten et al, 1963;Burge and Amery, 1973). Evidence has been presented that other agents may be involved (Marchand, 1955;Palmer, 1960;Cox, 1961;Squire et al, 1968;Collis, 1970;Gillison et al, 1971;Henderson et al, 1973;Stol et al, 1974). Bile, among…”
Section: Bile Salt Concentration a Total Bile Salts (Fasting)mentioning
confidence: 99%
“…He documented high acid secretion in many of his patients, but many had concurrent duodenal ulcers. When ulcer patients are excluded, others have reported that stimulated acid secretion is normal in patients with hiatus hernia (Williams et al 1967, Squire et al 1968). Our own data indicate no difference between normal subjects and those with hiatus hernia in terms of maximal acid output stimulated by pentagastrin or histamine.…”
Section: Gastric Acid Secretionmentioning
confidence: 99%